Barriers and Limitations of Mentoring in Polish Organizations - Joanna Mesjasz (Forum Oświatowe, 2013)
In Polish organizations one can recognize a lot of barriers in the mentoring implementation. According to the author, at the root of these barriers are hierarchies of values: social, national, organizational, and hierarchies of values represented by individual employees. The purpose of this article is to trace the sources of constraints in the mentoring implementation process. The analysis is carried out on several levels: from the broadest social perspective, through the national to the perspective of the organization. In the article, there are also presented actions that should be taken by Polish organizations to overcome barriers and constraints in the mentoring implementation process.